IDB Regional Strategy for Support to the Caribbean Community 2007-2010 (IDB [Washington]US, 2006)
Offers proposals on how to use the Bank's various financial and non-financial instruments to support priority areas of action related to regional integration and, where possible, indicates how those instruments can be mutually supportive. Highlights the importance of integrating regional objectives into the Bank's programming, and offers specific recommendations on how to achieve this.
Keywords: IDB